2019
DOI: 10.1371/journal.pone.0225163
|View full text |Cite
|
Sign up to set email alerts
|

Psychosocial determinants of sustained maternal functional impairment: Longitudinal findings from a pregnancy-birth cohort study in rural Pakistan

Abstract: Function is an important marker of health throughout the life course, however, in low-and-middle-income-countries, little is known about the burden of functional impairment as women transition from pregnancy to the first year post-partum. Leveraging longitudinal data from 960 women participating in the Share Child Cohort in Pakistan, this study sought to (1) characterize functional trajectories over time among women in their perinatal period and (2) assess predictors of chronic poor functioning following child… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 45 publications
1
6
0
Order By: Relevance
“…In our study, relative to the well-functioning trajectory, women with lower education level were more likely to belong to the very poor functional trajectory group as compared with women with higher education status. This is in line with the results of previous studies, which reported that high level of education was associated with greater functional status 16 49 55. This might be due to the fact that higher education may enhance resilience and significantly increase likelihood of recovery.…”
Section: Discussionsupporting
confidence: 92%
See 2 more Smart Citations
“…In our study, relative to the well-functioning trajectory, women with lower education level were more likely to belong to the very poor functional trajectory group as compared with women with higher education status. This is in line with the results of previous studies, which reported that high level of education was associated with greater functional status 16 49 55. This might be due to the fact that higher education may enhance resilience and significantly increase likelihood of recovery.…”
Section: Discussionsupporting
confidence: 92%
“…Additionally, we required at least 10% of the sample to be present in a particular group and all trajectories were distinct from one another by visual assessment of trajectory figures looking for non-overlapping confidence intervals 46. The labelling of each trajectory was based on a previous research work 49…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…In LMIC, home violence in the form of interpersonal violence is particularly common, which is also re ected in our sample (51,52). Home violence was the only domain that signi cantly predicted cortisol, possibly because it is linked to consequences that are emotional in nature: isolation, fear, guilt, low self-esteem (53).…”
Section: Discussionmentioning
confidence: 54%
“…High values of entropy (> .80) indicate that individuals are classified with confidence (i.e., the model is generally pretty sure that persons belong to a particular class) and there is adequate separation between the latent classes [ 66 ]. Additionally, we required at least 5% of the sample to be present in a particular group and all trajectories were distinct from one another by visual assessment of trajectory figures looking for nonoverlapping confidence intervals [ 65 , 67 , 68 ]. The labeling of each trajectory was based on a previous research work [ 1 ].…”
Section: Methodsmentioning
confidence: 99%